Individual and community level factors associated with use of iodized salt in sub-Saharan Africa: A multilevel analysis of demographic health surveys. - Yigizie Yeshaw (Public Library of Science (PLoS), 2021)
Introduction Iodine deficiency disorder a common problem in sub-Saharan Africa (SSA). It affects not only the health of the affected individual but also the economic development of the country. However, to the best of our knowledge, there is a scarcity in literature about the associated factors of iodized salt utilization in sub-Saharan Africa. Therefore, this study aimed to identify both individual and community level determinants of iodized salt utilization in sub-Saharan Africa. Methods This study used the appended datasets of the most recent demographic and health survey from 31 sub-Saharan countries. A total weighted sample of 391,463 households was included in the study. Both bivariable and multivariable multilevel logistic regression were done to determine the associated factors of iodized salt utilization in SSA. P value ≤ 0.05 was used to declare statistically significant variables. Results Those households with primary (AOR  =  1.53, 95% CI  =  1.50-1.57), secondary (AOR  = 1.81, 95% CI  =  1.76-1.86) and higher education level (AOR  =  2.28, 95% CI  =  2.17-2.40) had higher odds of iodized salt utilization. Households with middle (AOR  =  1.05, 95% CI  =  1.02-1.08), richer (AOR  = 1.13, 95% CI  =  1.09-1.17) and richest wealth index (AOR  =  1.23, 95% CI  =  1.18-1.28) also had an increased chance of using iodized salt. Households from high community media exposure (AOR  =  2.07, 95% CI  =  1.71-2.51), high community education level (AOR  =  3.78, 95% CI  =  3.14-4.56), and low community poverty level (AOR = 1.29, CI  =  1.07-1.56) had higher odds of using salt containing iodine. Conclusion Both individual and community level factors were found to be associated with use of salt containing iodine in sub-Saharan Africa. Education level, media exposure, community poverty level, wealth index, community education, and community media exposure were found to be associated with use of salt containing iodine in SSA. Therefore, to improve the use of iodized salt in the region, there is a need to increase access to media sources and develop the socioeconomic status of the community.